The multi-dimensional large deviations of Linnik type on some regions - Vilkauskas, L. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Л. Вилкаускас. Большие уклонения типа Линника в многомерном случае на некоторых областяхL. Vilkauskas. Daugiamačiai Liniko tipo dideli atsilenkimai